The effect of 'allergenic' and 'nonallergenic' antibiotics on dog keratinocyte viability in vitro. Issue 5 (11th September 2013) - Voie, Katrine L.; Lucas, Benjamin E.; Schaeffer, David; Kim, Dewey; Campbell, Karen L.; Lavergne, Sidonie N.
<x xml:space="preserve">Abstract</x> Background Immune‐mediated adverse drug reactions (drug hypersensitivity) are relatively common in veterinary medicine, but their pathogenesis is not well understood. For an unknown reason, delayed drug hypersensitivity often targets the skin. Antibiotics, especially β‐lactams and sulfonamides, are commonly associated with these adverse events. The 'danger theory' hypothesizes that 'danger' signals, such as drug‐induced cell death, might be part of the pathogenesis of drug hypersensitivity reactions. Hypothesis/Objectives The goal of this study was to determine whether antibiotics that are commonly associated with cutaneous drug hypersensitivity (allergenic) decrease canine keratinocyte viability in vitro more than antibiotics that rarely cause such reactions (nonallergenic). Methods Immortalized canine keratinocytes (CPEK cells) were exposed to a therapeutic range of drug concentrations of four 'allergenic' antibiotics (two β‐lactams, i.e. amoxicillin and cefalexin, and two sulfonamides, i.e. sulfamethoxazole and sulfadimethoxine) or two 'nonallergenic' antibiotics (enrofloxacin and amikacin) over 48 h (2, 4, 8, 24 and 48 h). The reactive nitroso metabolite of sulfamethoxazole was also tested. Results Cefalexin (2 mmol/L) significantly decreased cell viability after 48 h (28 ± 7%; P = 0.035). The nitroso metabolite of sulfamethoxazole (100 μmol/L) decreased cell viability after 2 h (21 ± 7%; P = 0.049), but cell numbers were increased after 8 h (22 ± 6%; P = 0.018). In addition, enrofloxacin (500 μmol/L) also significantly decreased cell viability by 37% (±6%; P = 0.0035) at 24 h and by 70% (±8%; P < 0.001) at 48 h. Conclusion It appears that the effect of drugs on the in vitro viability of dog keratinocytes is not a good predictor of the 'allergenic' potential of an antibiotic. Further work is required to investigate other drug‐induced 'danger' signals in dog keratinocytes exposed to 'allergenic' antibiotics in vitro.